Answer:
x = - 3
Step-by-step explanation:
g(x) = 4x + 1...... (1)
g(x) = -11.... (2)
From equations (1) & (2)
-11 = 4x + 1
-11 - 1 = 4x
-12 = 4x
-12/4 = x
-3 = x
x = - 3
Answer:
Step-by-step explanation:
y = 2x - 1
y = x - 8 ------ (i)
substitute y = 2x - 1 in equation (i)
2x - 1 = x - 8
2x = x - 8 + 1
2x = x - 7
2x - x = -7
x = -7
Substitute x value in equation (i)
y = -7 - 8
y = -15
Answer:5x-20y=12
Step-by-step explanation:
Answer:
Step-by-step explanation:
R(2,3) T(-3,-2) S(2,-2) here are your points.